THE SOUL OF MBIRA TWENTY YEARS ON: A RETROSPECT, Part 2: THE SOUL OF MBIRA: MUSIC AND TRADITIONS OF THE SHONA PEOPLE OF ZIMBABWE, by Paul Berliner, University of Chicago Press, Chicago and London, 1994 (first published Univ. of California Press, Berkeley, 1978), 312pp, illustrations, transcriptions, appendices, index. - Chernoff, John M. (International Library of African Music, 1996)
pages: 90-95
Keywords: Shona (African people); African Music; Zimbabwe